The Role of Civic Education In Developing The Moral Through Democracy Learning - Ani Sulianti; Samsul Arifin; Halimatus Sakdiyah (JED (Jurnal Etika Demokrasi), 2020)
This study aimed to understand1) The role of Civic Education in developing the students’ moral, 2) The application of Democracy learning in developing the students’ moral. The research methods used in this study was a qualitative method. The technique of collecting data used observation and interview. The technique of data processing using triangulation. The technique of the data analysis used data reduction, data display, and data conclusion drawing verification. The result of this study showed that 1) Civic Education is very influential in developing the students’ moral to interact with school and community or social environment 2) Democracy play an important role in developing their behaviour in social, tolerant, appreciate and respect each other.Keywords: Civic Education, Moral, and Democracy. Penelitian ini bertujuan untuk mengetahui: 1). Peran pendidikan kewarganegaraan dalam mengembangkan moral peserta didik, 2). Penerapan pembelajaran demokrasi dalam mengembangkan moral peserta didik. Metode penelitian yang digunakan yaitu metode kualitatif. Teknik pengumpulan data menggunakan observasi dan wawancara. Teknik pengolahan data menggunakan triangulasi. Teknik analisis data menggunakan data reduction, data display, and data conclusion drawing verification. Hasil penelitian menunjukkan bahwa 1). Pendidikan kewarganegaraan sangatlah berpengaruh dalam mengembangkan moral peserta didik dalam berinteraksi dengan lingkungan sekolah dan masyarakat 2). Demokrasi berperan penting dalam mengembangkan perilaku peserta didik dalam bersosial, bertoleransi, saling menghargai dan menghormati.Kata Kunci: Pendidikan Kewarganegaraan, Moral, Demokrasi.